Integrating psychiatry into basic clinical skills: A three‐year nationwide quantitative assessment of postgraduate training programs - Hidetaka Tamune; Hirohisa Fujikawa; Hiroyuki Harada; Tomoyuki Kodama; Masaaki Sasaki; Daichi Sone; Miwa Sekine; Masanobu Ito; Tadafumi Kato; Yuji Nishizaki; Yasuharu Tokuda (PCN Reports)
Abstract Aim The aim of this study was to develop quantitative outcome indicators for psychiatric training programs integrated into the General Medicine In‐Training Examination (GM‐ITE) and to investigate which characteristics correlate with high scores in psychiatry. Methods A nationwide cross‐sectional study was conducted over 3 fiscal years (2021–2023). An anonymous online questionnaire was distributed to postgraduate year 1 and 2 residents who completed the GM‐ITE. The primary outcome was GM‐ITE score, with a particular focus on psychiatry. Multiple‐choice questions for the psychiatry field were created by board‐certified psychiatrists with various subspecialties, then reviewed and piloted. Multiple regression analysis examined correlations between GM‐ITE score and various resident and facility characteristics. Results A total of 18,226 residents participated over the 3 years, of whom 5%–6% aspired to specialize in psychiatry. Quantitative scores were effective in the psychiatry field across all 3 years. Psychiatry aspirants had lower scores in internal medicine, emergency, and total scores but higher scores in psychiatry. Residents from university hospitals had lower psychiatry scores, while the number of psychiatry beds and supervising psychiatrists did not correlate with higher psychiatry scores. These findings indicate the need for psychiatric training programs distinct from general internal medicine and emergency training. Conclusion Based on these quantitative psychiatry scores, this study highlights the necessity of improving physical assessment skills during residency for psychiatry aspirants, who score higher in psychiatry. Future research should identify effective training programs and facility practices that lead to higher psychiatry scores among residents, and thereby better integrate psychiatry into basic clinical skills.